(untitled) (UMRAN - Journal of Islamic and Civilizational Studies, 2026)
Jawi is a national heritage asset rich in intellectual, historical and Malay-Islamic cultural values. Despite various initiatives implemented at the scholl level, the continuity of Jawi education in higher education institutions (HEIs) remains limited and receives insufficient attention. This study aims to explore the current status of Jawi within higher education and propose future strategies to elevate Jawi education in Malaysia HEIs. A qualitative approach was employed through semi-structured interviews with lecturers involved in Jawi teaching. The data analyzed using the constant comparataive method and triangulated with document analysis. The finding reveals that the understanding of Jawi needs to be reframed beyond its perception as merely a script. Jawi education in HEIs is not fully integrated into the mainstream curriculum but it mostly offered as elective or minor courses. These findings underscore the need for reform in alternative teaching guidelines that are holistic, contextual, and responsive not only to preserve the Jawi heritage but also to adapt it to 21st-century learning requirements. The adoption of learner-centered andragogical approaches should be prioritized. This study proposes the development of a Jawi education model framework grounded in Islamic epistemology, andragogical principles and the strengthening of higher education policy. Such an initiave is deemed crucial to ensure the continued relevance of Jawi as a medium of heritage, thought and identity in the modern educational era.